TINGKAT KEPUASAN KONSUMEN TERHADAP PELAYANAN DI RUMAH KOPI BILLY JALAN 17 AGUSTUS KOTA MANADO - Ramli, Irfandi; Ngangi, Charles Reijnaldo; Maweikere, Audrey Julia Maria (AGRI-SOSIOEKONOMI, 2022)
This study aims to determine the level of consumer satisfaction with services at Rumah Kopi Billy Jalan 17 Agustus Manado City. The research lasted for 2 months and was carried out from September to October 2021. The data collected, namely primary data, was obtained from direct interviews with consumers as visitors by using a questionnaire. Secondary data were obtained from coffee house owners as well as data related to research taken from the internet. Sampling was doneby accidental sampling as many as 5 respondents every day from Monday to Saturday which could be found so that the number of respondents was 30 people. The results showed that the level of consumer satisfaction with services at the Rumah Kopi Billy Jln 17 Agustus, Manado was included in the satisfied category with a satisfaction index of 77.68% based on product, price, place, promotion and service quality.